Computational appraisal of fluid flow behavior in two-sided oscillating lid-driven cavities. (15th April 2021) - Bhopalam, Sthavishtha R.; Perumal, D. Arumuga; Yadav, Ajay Kumar
Highlights: Lattice Boltzmann method is used to compute flow in oscillating lid-driven cavities. Two-sided oscillating lids with parallel and antiparallel motions are considered. The effects of Reynolds number, oscillating frequency and speed ratio are studied. The flow modes for these parameters are showcased using three-dimensional flow maps. Current results can be used for benchmarking numerical solvers in oscillatory flows. Abstract: The current work employs lattice Boltzmann simulations to compute incompressible flows in two-sided oscillating lid-driven cavities. Vortex dynamics in oscillatory lid-driven cavity flows is more complex than steady lid-driven cavity flows due to the strong dependence of the evolutionary flow field on several parameters of interest: Reynolds number ( Re ), dimensionless oscillating frequency ( ῶ ) and Speed Ratio ( SR ), to name a few. A comprehensive study on the variation of flow patterns in both antiparallel and parallel oscillating wall motions has been performed by systematically varying the parameters ( Re, ῶ and SR ) over a wide range of values. To make it easier for the reader, these flow patterns have been appropriately classified into several flow modes, which are later explained using streamline patterns, centerline velocity profiles and three-dimensional flow maps. Simulations show that Re and ῶ control the penetration depth of the fluid inside the cavity, while SR controls the size and strength of additional primary or corner vortices generated from the bottom lid motion. The significance of the current work may be found in industrial applications, where Re, ῶ and SR may have to appropriately tuned to yield a specific flow mode. Graphical abstract: Image, graphical abstract